Preliminary Study of gastric ulcers in horses of the National Police MEBUC Carabineros Floridablanca, Santander - Suárez Guerrero, Jesús Leonardo; Bedoya Ríos, Miguel Ángel; Gómez Celis, Joaquín; Duarte, Luz Zoraya (Spei Domus, 2020)
The aim: this paper is to present a literature review with gastric ulcers syndrome in three horses of Argentine saddle belonging to Fort Asturias Carabineros Floridablanca Santander. Topics: where a clinical examination, patient assessment through clinical history, anamnesis is made, it becomes gastroscopy in Agricultural Academic Center that Universidad Cooperativa de Colombia, in clinical large animal, is located in the municipality of Piedecuesta, Guatiguará Department of Santander, subsequent biopsies of the two parts of the stomach lining is done sent histopathology in order to give a more accurate and reliable diagnosis. Development: gastric ulcer syndrome (EGUS) is a pathology that is on the rise in the equine industry, affecting the two regions of the mucosa of the stomach and proximal duodenum. This disease affects both foals and adult horses. It has a high incidence of disease affecting 53% to 93% of the population. It´s a multifactorial syndrome, may occur due to intense exercise, high-carbohydrate rations, meals at odd times, stress, continuous use of NSAIDs, transportation, changes in diet, frequent cramps. Conclusions: this clinical study reports not only observed gastritis, gastric ulcers if not in healing, erythema, elevated lesions, and fibrinogen, which corroborate described by each of the authors in literature review.